Extreme Elevations in Blood Pressure and All-Cause Mortality in a Referred CKD Population: Results from the CRISIS Study - James Ritchie; Francesco Rainone; Darren Green; Helen Alderson; Diana Chiu; Rachel Middleton; Donal O’Donoghue; Philip A. Kalra (International Journal of Hypertension)
Hypertension frequently complicates chronic kidney disease (CKD), with studies showing clinical benefit from blood pressure lowering. Subgroups of patients with severe hypertension exist. We aimed to identify patients with the greatest mortality risk from uncontrolled hypertension to define the prevalence and phenotype of patients who might benefit from adjunctive therapies. 1691 all-cause CKD patients from the CRISIS study were grouped by baseline blood pressure—target (<140/80 mmHg); elevated (140–190/80–100 mmHg); extreme (>190 and/or 100 mmHg). Groups were well matched for age, eGFR, and comorbidities. 77 patients had extreme hypertension at recruitment but no increased mortality risk (HR 0.9, P=0.9) over a median follow-up period of 4.5 years. The 1.2% of patients with extreme hypertension at recruitment and at 12-months had a significantly increased mortality risk (HR 4.3, P=0.01). This association was not seen in patients with baseline extreme hypertension and improved 12-month blood pressures (HR 0.86, P=0.5). Most CKD patients with extreme hypertension respond to pharmacological blood pressure control, reducing their risk for death. Patients with extreme hypertension in whom blood pressure control cannot be achieved have an approximate prevalence of 1%. These patients have an increased mortality risk and may be an appropriate group to consider for further therapies, including renal nerve ablation.